Synthesis, characterization, and demulsification of water in crude oil emulsion via a corn oil-based demulsifier - M. A., Saadiah; Nour, Abdurahman Hamid; Rosli, Mohd Yunus (Elsevier Ltd, 2021)
Natural product-based materials have gained significant interest in replacing the petroleum-based oil chemicals with environmentally friendly materials. A corn oil-based demulsifier has been successfully synthesized by the condensation reaction of corn oil with diethanolamine in the presence of a catalyst applied during separation via a water-in-oil (W/O) emulsion. The demulsifier was characterized by FTIR, GC-MS, and LC-QTOF-MS analyses. The surfactant's separation efficacy was studied using the Sany-glass test. The results showed that this new product efficiently demulsified the W/O emulsion with 98% separation achieved. The influence of settling time, demulsifier dosage, and temperature on the demulsification efficiency were investigated. The separation efficiency increased with increasing settling time, demulsifier dose and the temperature conditions accelerate the demulsification process. As well, the interfacial tension decreases with increases of the demulsifier dose